Maternal and Perinatal Outcome in Twin Pregnancy - Kaphle, Pratibha; Baral, Gehanath; Chaudhary, Amar Nath; Acharya, Sandeep (Journal of Nobel Medical College, 2025)
Background: The incidence of twin pregnancy has significantly risen over past decade along with the use of various assisted reproductive technologies. Twin pregnancy is associated with increased maternal and perinatal complications and is a high-risk pregnancy which necessitates close supervision of both mother and fetuses during antenatal period. This study aims to evaluate maternal and perinatal outcome of twin pregnancy.Materials and Methods: This was the observational cross-sectional study conducted in 130  pregnant women with twin pregnancy ≥28weeks gestation in Department of Obstetrics and Gynecology from 24 March 2024 to 24 March 2025 at Nobel Medical College Teaching Hospital, Biratnagar, Nepal. Data were collected defining various maternal and neonatal characteristics and outcomes were evaluated in terms of maternal complications and obstetric outcome and statistical analysis was performed for comparison of perinatal outcomes between twins.Results: Out of total 7006 births during this period, 130 were twin pregnancies and 2were triplets. The incidence of twins was 1.85%. The most common maternal complications observed was preterm labor (44.6%) followed by PROM (16.1%), hypothyroidism (13%), pregnancy induced hypertension (13%), anemia (8.4%), and PPH (8.4%). The most common mode of delivery was cesarean section in 91 females. Among the fetal complications low birth weight was seen as the most common complication in both twins. In first twin, low birth weight, respiratory distress, neonatal sepsis, and NICU admission were seen in 83.8%, 22.3%, 13.8% and 18.4% respectively and was higher than second twin. Similarly, intrauterine fetal demise and low Apgar score at 5 min  was 3.8% and 18.4% in second twin and was higher than the first one. Perinatal mortality was similar in both twins. Prolonged NICU stay was seen in second twin.Conclusion: Preterm labor was the most common maternal complication while Low Birth Weight as a sequelae of prematurity was most common complication of both twins. RDS and sepsis was higher in first twin while low APGAR @ 5 min was higher in second twin. Considering high risk pregnancy, special care for mothers with twin pregnancies is necessary to mitigate adverse pregnancy outcomes.